Changes in Unfrozen Water Contents in Warming Permafrost Soils - Evgeny Chuvilin; Natalia Sokolova; Boris Bukhanov (Geosciences, 2022)
Climate warming in the Arctic, accompanied by changes in permafrost soil properties (mechanical, thermal, filtration, geophysical), is due to increasing unfrozen pore water content. The liquid component in frozen soils is an issue of key importance for permafrost engineering that has been extensively studied since the beginning of the 20th century. We suggest a synthesis and new classification of various experimental and calculation methods for the determination of unfrozen water content. Special focus is placed on the method of applying measurements to the water potential, which reveals the impact of permafrost warming on unfrozen water content. This method was applied to natural soil samples collected from shallow permafrost from northern West Siberia affected by climate change, and confirms the revealed trends. The obtained results confirm that unfrozen water content is sensitive not only temperature but also particle size distribution, salinity, and the organic matter content of permafrost soils.